Analysis of Individual Factors Influencing Musculoskeletal Disorder Complaints Among Grab-Bike Online Motorcycle Drivers in Purwokerto - Wulandari, Putri; Harwanti, Siti; Suryanto, Suryanto (Lambung Mangkurat University, 2025)
Musculoskeletal disorders (MSDs), characterized by pain, stiffness, numbness, and other physical discomforts in the muscles and supporting structures, are prevalent among online motorcycle drivers due to prolonged sitting, limited rest, and repetitive movements. This study aimed to analyze individual factors associated with MSDs complaints among Grab-Bike drivers in Purwokerto, Indonesia. A cross-sectional study was conducted using accidental sampling with 77 respondents from a population of 330 drivers. Data were collected using the Nordic Body Map (NBM) questionnaire and analyzed through univariate, bivariate (chi-square and Spearman correlation), and multivariate (multiple logistic regression) analyses. The findings showed that the factors influencing MSDs complaints were age (p value = 0.042), work tenure (p value = 0.026), body mass index (BMI) (p value =0.182), smoking habits (p value =0.895), exercise habits (p value =0.863), and history of MSDs (p value = 0.529). Age and work tenure were significantly associated with MSDs complaints, while, BMI, smoking habits, exercise habits, and history of MSDs showed no significant association. The most influential factor was work tenure (OR = 6.340). Daily working hours adjustments and regular health monitoring are recommended to reduce MSDs risks in this occupational group.